VISUALIZATION OF Nd3+-DOPED LaF3 NANOPARTICLES FOR NEAR INFRARED BIOIMAGING VIA UPCONVERSION LUMINESCENCE AT MULTIPHOTON EXCITATION MICROSCOPY - A. V. Ryabova; K. Keevend; E. Tsolaki; S. Bertazzo; D. V. Pominova; I. D. Romanishkin; P. V. Grachev; V. I. Makarov; I. A. Burmistrov; A. S. Vanetsev; E. O. Orlovskaya; A. E. Baranchikov; et al. (Biomedical Photonics, 2018)
Recent developments in the field of biophotonics facilitate the raise of interest to inorganic nanoparticles (NPs) doped with Nd3+ ions, because of their near-infrared (NIR) absorption. These NPs are interesting bioimaging probes for deep tissue visualization, while they can also act as local thermometers in biological tissues. Despite the good possibilities for visualization of NPs with Nd3+ ions in NIR spectral range, difficulties arise when studying the cellular uptake of these NPs using commercially available fluorescence microscopy systems, since the selection of suitable luminescence detectors is limited. However, Nd3+ ions are able to convert NIR radiation into visible light, showing upconversion properties. In this paper we found optimal parameters to excite upconversion luminescence of Nd3++:LaF NPs in living cells and to compare the distribution of the NPs inside the cell culture of human macrophages THP-1 obtained by two methods. Firstly, by detecting the upconversion luminescence of the NPs inVIS under NIR multiphoton excitation using laser scanning confocal microscopy and secondly, using transmission electron microscopy.